PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH IPO PADA PERUSAHAAN MANUFAKTUF DI BEI - Kusumah, Voni Gusti; Ramayani, S.Pd., M.E, Citra; Utami, S.E., MBA, Hayu Yolanda (Pendidikan Ekonomi, 2014)
Â ABSTRACTÂ This study aims to distinguish : Financial performance before and after the IPO at a manufacturing company in the Stock Exchange . This type of research is the study of this research is kuantitatif.Populasi throughout the entire manufacturing companies listed on the Stock Exchange , amounting to 39 perusahaan.Teknik sampling with purposive sampling with a sample size of 10 companies . Data analysis techniques : kompratif analysis or comparison , the normality test, paired sample t - test with SPSS version 16 . Results showed that : 1 ) There are no significant differences anatara Ratio Curent value of the company before and after an IPO is sig value 0.000 < 0.05 then the decision is Ho rejected and Ha accepted . 2 ) There are no significant differences between Equty Debt Ratio value of the company before and after an IPO is sig 0.000 < 0.05 then the decision is rejected Ho Ha received . 3 ) There is a significant difference between Total Assets Over Trun owned enterprises before and after the IPO mealkukan ie the value 0.011 < 0.05 then Ho is rejected and Ha decision is received . 4 ) Based On Equity Retrun testing the sig 0.203 > 0.05 means that Ho is accepted Ha rejected . In this research the company to continue to maintain the stability of the financial performance of the company after the IPO held as maintaining liquidity , solvency , and profitability . It is important that investor confidence held or finance company can be filled so that the existence of the company can be maintained within a panajang . For investors it is recommended that a comprehensive analysis and make stock portfolio before making an investment decision on one of the companies doing an IPO . It is important that the values held later the losses can be minimized and the value obtained financial investors can be maximized .